Printability, Durability, Contractility and Vascular Network Formation in 3D Bioprinted Cardiac Endothelial Cells Using Alginate–Gelatin Hydrogels - Roche, Christopher David; Sharma, Poonam; Ashton, Anthony Wayne; Jackson, Chris; Xue, Meilang; Gentile, Carmine (Frontiers in Bioengineering and Biotechnology, 2021)
BACKGROUND: 3D bioprinting cardiac patches for epicardial transplantation is a promising approach for myocardial regeneration. Challenges remain such as quantifying printability, determining the ideal moment to transplant and promoting vascularisation within bioprinted patches. We aimed to evaluate 3D bioprinted cardiac patches for printability, durability in culture, cell viability and endothelial cell structural self-organisation into networks. METHODS: We evaluated 3D-bioprinted double-layer patches using alginate/gelatine (AlgGel) hydrogels and three extrusion bioprinters (REGEMAT3D; INVIVO; BIO X). Bioink contained either neonatal mouse cardiac cell spheroids or free (not-in-spheroid) human coronary artery endothelial cells with fibroblasts, mixed with AlgGel. To test effects on durability, some patches were bioprinted as a single layer only, cultured under minimal movement conditions or had added fibroblast-derived extracellular matrix hydrogel (AlloECM). Controls included acellular AlgGel and gelatin methacryloyl (GELMA) patches. RESULTS: Printability was similar across bioprinters. For AlgGel compared to GELMA: resolutions were similar (200-700μm line diameters), printing accuracy was 45% and 25%, respectively (AlgGel was 1.7x more accurate;p<0.05), shape fidelity was 92% (AlgGel) and 96% (GELMA);p=0.36. For durability, AlgGel patch median survival in culture was 14 days (IQR:10-27) overall which was not significantly affected by bioprinting system or cellular content in patches. We identified three factors which reduced durability in culture: 1) bioprinting one layer depth patches (instead of two layers); 2) movement disturbance to patches in media; 3) the addition of AlloECM to AlgGel. Cells were viable after bioprinting followed by 28 days in culture and all BIO X-bioprinted mouse cardiac cell spheroid patches presented contractile activity starting between day 7 and 13 after bioprinting. At day 28, endothelial cells in hydrogel displayed organisation into endothelial network-like structures. CONCLUSIONS: AlgGel-based 3D bioprinted heart patches permit cardiomyocyte contractility and endothelial cell structural self-organisation. After bioprinting, a period of 2 weeks' maturation in culture prior to transplantation may be optimal, allowing for a degree of tissue maturation but before many patches start to lose integrity. We quantify AlgGel printability and present novel factors which reduce AlgGel patch durability (layer number, movement and the addition of AlloECM) and factors which had minimal effect on durability (bioprinting system and cellular patch content).